Penerapan Senam Lansia Pada Lansia Insomnia Di Desa Pilangsari Kabupaten Sragen - Wijayanti, Tri; Husain, Fida’ (Pusat Riset dan Inovasi Nasional, 2023)
Background: feeling sleepy every day is the impact of sleep disturbance at night (insomnia), and can interfere with daily activities. Insomnia can cause other effects such as anxiety, stress, and ending with depression. In the elderly, sleep disturbances can cause various kinds of degenerative diseases that have been suffered and become uncontrolled. Treatment of insomnia disorder is carried out with non-pharmacological treatment, one of the non-pharmacological therapies that can be done is Elderly Exercise. Objective: To determine changes in the level of insomnia in the elderly before and after doing Elderly Exercise. Method: This application uses a descriptive method on 2 respondents, carried out 6 times in 2 weeks. The instrument used was KSPBJ-IRS (Jakarta Biological Psychiatric Study Group-Insomnia Rating Scale). Results: Treatment of insomnia disorder with Elderly Gymnastics given 6 times for 2 weeks in 30-45 minutes can affect the level of the respondent's sleep quality What specific exercises were included in the Elderly Gymnastics therapy?y so that there is a change in the elderly insomnia scale. Conclusion: the application shows that after the Elderly Seam was carried out 6 times in 2 weeks within 30-45 minutes there was a decrease in the insomnia scale in both respondents.